Plasma Processing with Fluorine Chemistry for Modification of Surfaces Wettability - Satulu, Veronica (Molecules, 2016)
Using plasma in conjunction with fluorinated compounds is widely encountered in material processing. We discuss several plasma techniques for surface fluorination: deposition of fluorocarbon thin films either by magnetron sputtering of polytetrafluoroethylene targets, or by plasma-assisted chemical vapor deposition using tetrafluoroethane as a precursor, and modification of carbon nanowalls by plasma treatment in a sulphur hexafluoride environment. We showed that conformal fluorinated thin films can be obtained and, according to the initial surface properties, superhydrophobic surfaces can be achieved.